"Real-World" Application of Thrombolysis in Cardiac Arrest. (June 2020) - Smith, Susan E.; Johnson, Daniel C.
Background: Current guidelines recommend consideration of thrombosis as a reversible cause of cardiac arrest. The use of thrombolytic therapy during cardiac arrest, however, is controversial. Objective: We sought to characterize the use of thrombolytic therapy during cardiac arrest and to evaluate the rate of return of spontaneous circulation (ROSC) in a "real-word" setting. Methods: A single-center, retrospective, cohort study of adult patients who received alteplase during cardiac arrest between 2010 and 2015 were performed at a tertiary academic medical center. Results: Twenty-six patients were identified. Patients were predominantly male (65%) and Caucasian (89%) and were a median age of 64 years. Five patients had a history of preexisting venous thromboembolism, and eight patients were receiving systemic anticoagulation. Pulmonary embolism was confirmed prior to the administration of alteplase in 5 patients. The median dose of alteplase administered was 100 mg. ROSC was achieved in 65% of patients, 2 of whom survived to hospital discharge. Both surviving patients experienced a bleeding event. Conclusion: In a single center's experience, thrombolytic therapy is used infrequently for the management of cardiac arrest. Thrombolysis during cardiac arrest should be considered on a case-by-case basis and should be utilized only when there is a high suspicion for pulmonary embolism as the cause of arrest and when thrombolytic therapy is readily available.